2016
DOI: 10.1152/ajpcell.00318.2015
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction analysis of the effects of myosin regulatory light chain phosphorylation and butanedione monoxime on skinned skeletal muscle fibers

Abstract: The phosphorylation of the myosin regulatory light chain (RLC) is an important modulator of skeletal muscle performance and plays a key role in posttetanic potentiation and staircase potentiation of twitch contractions. The structural basis for these phenomena within the filament lattice has not been thoroughly investigated. Using a synchrotron radiation source at SPring8, we obtained X-ray diffraction patterns from skinned rabbit psoas muscle fibers before and after phosphorylation of myosin RLC in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 84 publications
2
20
0
Order By: Relevance
“…7d1, 2, 10d, 11b) (Linari et al 2015). Seventh, X-ray diffraction of rabbit skeletal muscle suggests that RLC phosphorylation move heads away from thick towards thin filaments (Yamaguchi et al 2016) confirming tarantula equatorial X-ray diffraction results . Eighth, spectroscopic studies of the super-relaxed state of skeletal muscle supports the putative RLC-RLC interface identified by cryo-EM showing that both the divalent cation bound to RLC and the RLC NTE play a role in the stability of the superrelaxed state (Nogara et al 2016).…”
Section: Interactions Form Ihms and Their Helical Tracks In The Relaxmentioning
confidence: 72%
See 2 more Smart Citations
“…7d1, 2, 10d, 11b) (Linari et al 2015). Seventh, X-ray diffraction of rabbit skeletal muscle suggests that RLC phosphorylation move heads away from thick towards thin filaments (Yamaguchi et al 2016) confirming tarantula equatorial X-ray diffraction results . Eighth, spectroscopic studies of the super-relaxed state of skeletal muscle supports the putative RLC-RLC interface identified by cryo-EM showing that both the divalent cation bound to RLC and the RLC NTE play a role in the stability of the superrelaxed state (Nogara et al 2016).…”
Section: Interactions Form Ihms and Their Helical Tracks In The Relaxmentioning
confidence: 72%
“…7d) (Brito et al 2011) suggested a cooperative phosphorylation mechanism for activation of tarantula thick filaments (Sulbarán et al 2013) extended by further work (Espinoza-Fonseca et al 2007, 2008Kast et al 2010;Alamo et al 2015Alamo et al , 2016Yamaguchi et al 2016). The CPA mechanism is shown in Fig.…”
Section: Interactions Form Ihms and Their Helical Tracks In The Relaxmentioning
confidence: 83%
See 1 more Smart Citation
“…The M·ADP·Pi state is one of the states that favor the ‘closed’ conformation, but this conformation is also favored by the presence of so-called phosphate analogs, i.e., aluminofluoride and beryllium fluoride [ 18 ], and a myosin inhibitor blebbistatin [ 19 ], resulting in an increased helical order. An increased helical order is also observed in the presence of BDM [ 20 ]. Here the ‘closed’ conformation refers to the one consisting of “the switch-2 element of myosin head being in a position that interacts with the γ-phosphate-binding pocket; open conformation, the switch-2 loop being rotated away ~4 Å from the γ-phosphate-binding pocket, facilitating phosphate release” (quoted from ref.…”
mentioning
confidence: 99%
“…The wavelength and the size of X-ray beam was 0.09 nm and size, 250 × 150 µm, respectively, and the specimen-to-detector distance was 1.8 m. The fiber was kept at its slack length Lo (~3 mm) at a sarcomere length of 2.0-2.4 µm, which was measured by optical diffraction by He-Ne laser light [9]. Dithiothreitol (5 mM) and catalase (1000 U/mL) were added to the experimental solution to prevent damage of the fibers from free radicals produced by X-rays [25].…”
Section: Recording Of X-ray Diffraction Pattern From Rigor Fibers Befmentioning
confidence: 99%